Gender Identities in Jordanian Jokes - Al-Badawi, Mohammed; Sadeq, Alleddin; Abu Hatab, Wafa (Dirasat: Human and Social Sciences, 2021)
This paper aims at investigating the projections of gendered identities in Arabic Jordanian jokes. The data of this study consists of jokes that were selected from an online source for Arabic jokes based on the gender of the subject in the joke and the linguistic variety used. All the jokes have been analyzed in light of the General Theory of Verbal Humour (GTVH) that has been used as a theoretical framework to illustrate the ground-breaking characteristics of these new jokes and to contrast them with the traditionally gendered ones. The analysis of online Jordanian Arab jokes has revealed a patriarchal, often misogynistic perspective in jokes with rural lifestyle – which is usually known as the target of jokes in Jordan. On the other hand, modern jokes posted on the website Arabjokes.net that were analyzed in this study, give evidence of new tendencies – especially feminine in the humorous doing of gender, i.e. gender identities in Jordanian jokes. The analysis also validates the use of GTVH which is developed as a linguistic tool to capture joke (dis)similarity.